Proceedings of the 21th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2015
DOI: 10.1145/2783258.2783397
|View full text |Cite
|
Sign up to set email alerts
|

Instance Weighting for Patient-Specific Risk Stratification Models

Abstract: Accurate risk models for adverse outcomes can provide important input to clinical decision-making. Surprisingly, one of the main challenges when using machine learning to build clinically useful risk models is the small amount of data available. Risk models need to be developed for specific patient populations, specific institutions, specific procedures, and specific outcomes. With each exclusion criterion, the amount of relevant training data decreases, until there is often an insufficient amount to learn an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Different systems have differing data distributions [ 53 ] and collected attributes, impacting the performance and applicability of a model trained using one system’s data for another system [ 54 - 57 ]. To address these two issues, one can perform transfer learning and use other source systems’ information to improve model accuracy for the target system [ 54 , 58 , 59 ]. Transfer learning typically requires using other source systems’ raw data [ 60 , 61 ].…”
Section: Limitations Of Current Patient Identification Methods For Asmentioning
confidence: 99%
“…Different systems have differing data distributions [ 53 ] and collected attributes, impacting the performance and applicability of a model trained using one system’s data for another system [ 54 - 57 ]. To address these two issues, one can perform transfer learning and use other source systems’ information to improve model accuracy for the target system [ 54 , 58 , 59 ]. Transfer learning typically requires using other source systems’ raw data [ 60 , 61 ].…”
Section: Limitations Of Current Patient Identification Methods For Asmentioning
confidence: 99%
“…Likewise, authors in [24] proposed an approach that models the mortality probability as a latent state that evolves over time. Authors in [25] proposed an approach to address the problem of small data using transfer learning in the context of developing risk models for cardiac surgeries. They explored ways to build surgeryspecific and hospital-specific models using information from other kinds of surgeries and other hospitals.…”
Section: A Mortality Predictionmentioning
confidence: 99%
“…Following [25], in this work we use feature transference, but in a quite different way, as follows: (i) instead of applying instance weighting, we employed a deep model that transfers domain-shared features; (ii) we studied a broader scenario that includes diverse ICU domains; and (iii) our models employ both spatial and temporal feature extraction, being able to predict patient outcomes dynamically.…”
Section: A Mortality Predictionmentioning
confidence: 99%
“…15 Previously, transfer learning has been applied in the health care setting for segmenting magnetic resonance images across multiple scanners and postprocessing modes, 16 improving Clostridium difficile infection prediction performance using cross-institutional data, 17 creating time-varying risk assessment methods from EHR data, 18 and assessing the risk of adverse events in cardiac surgery. 19 However, there has been limited 2 Biomedical Informatics Insights work toward minimizing the data used in creating effective clinical decision support tools. 19 In this study, we build on our prior machine learning work in developing AutoTriage, an endto-end EHR-based algorithmic analysis system for forecasting patient mortality or predicting the results of intrahospital ward transfer and/patient discharge.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, there has been limited work toward minimizing the data used in creating effective clinical decision support tools. 19 In this study, we build on our prior machine learning work in developing AutoTriage , an end-to-end EHR-based algorithmic analysis system for forecasting patient mortality or predicting the results of intrahospital ward transfer and/patient discharge. For mortality prediction, we previously demonstrated that AutoTriage outperformed canonical risk scoring systems, SAPS II (the Simplified Acute Physiology Score 20 ), SOFA, MEWS, 6 and similarly outperformed MET and MEWS for discharge prediction.…”
Section: Introductionmentioning
confidence: 99%